Role of the municipal chief prosecutor to the infractions detected in the tax verifications (Review) (REDEL. Revista Granmense de Desarrollo Local, 2019)
This article refers to the role of the Municipal Chief Prosecutor in relation to the infractions detected in the tax verifications. In this regard, the legal and methodological foundations for the development of tax verifications and their directions are defined for their study; as well as the restoration of the broken legality and with it, the actions of the municipal chief prosecutor, both from a technical and management point of view, to achieve the restoration of the transgressed legality. The essential aspects for the control system and the plan of measures are offered. The study allows the deepening in the transformations occurred in each of the stages.
Keywords: chief prosecutor; tax verification; legality; control system.